2017
DOI: 10.1038/ncomms14209
|View full text |Cite
|
Sign up to set email alerts
|

A human immunodeficiency syndrome caused by mutations in CARMIL2

Abstract: Human T-cell function is dependent on T-cell antigen receptor (TCR) and co-signalling as evidenced by immunodeficiencies affecting TCR-dependent signalling pathways. Here, we show four human patients with EBV+ disseminated smooth muscle tumours that carry two homozygous loss-of-function mutations in the CARMIL2 (RLTPR) gene encoding the capping protein regulator and myosin 1 linker 2. These patients lack regulatory T cells without evidence of organ-specific autoimmunity, and have defective CD28 co-signalling a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
128
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(143 citation statements)
references
References 43 publications
11
128
0
4
Order By: Relevance
“…Previous studies demonstrated impaired T cell activation and effector functions in patients with CARMIL2 deficiencies [4,6]. Indeed, our patients presented with recurrent viral infections.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…Previous studies demonstrated impaired T cell activation and effector functions in patients with CARMIL2 deficiencies [4,6]. Indeed, our patients presented with recurrent viral infections.…”
Section: Resultsmentioning
confidence: 62%
“…The fundamental value of CARMIL2 for immune defense was also recently proven as patients with bi‐allelic CARMIL2 mutations were diagnosed. Although rare, reports of affected patients have recently been accumulating [1,4,6‐12]. CARMIL2 deficiency is characterized by the reduced regulatory T cell (T reg ) counts and impaired T cell activation, which is attributed to a defect in CD28‐mediated co‐stimulation [4,7‐9].…”
Section: Introductionmentioning
confidence: 99%
“…Patients lacked regulatory T-cells and suffered from immunodeficiency syndromes similar to those in patients in the studies discussed earlier (Sorte et al , 2016; Wang et al , 2016; Schober et al , 2017). In T-cells isolated from patients, levels of F-actin at the leading edge were decreased and the microtubule network was disorganized.…”
Section: Roles Of Carmils At the Cellular And Organismal Levelsmentioning
confidence: 75%
“…This molecule engages CD28 on the T cell surface to provide this critical second signal. An autosomal recessive loss‐of‐function mutation in capping protein regulator and myosin 1 linker 2 ( CARMIL2 ) encoding RGD, leucine‐rich repeat, tropomodulin and proline‐rich‐containing protein (RLTPR), a scaffolding protein necessary for CD28‐dependent activation of PI3K/PDK1/AKT in human T cells, was shown to cause a combined immunodeficiency . However, these patients also presented with severe atopic dermatitis, food allergy, significant elevations in IgE, allergic asthma, and cold urticaria.…”
Section: When Atopy Is In the Card(s)mentioning
confidence: 99%